(untitled) (Economic and Political Thought, 2016)
During the tenure of Foreign Minister Stefan Meller the decisions concerning Polish foreign policy were strongly influenced by frictions between particular policy-makers and between institutions forming Polish foreign policy. This new situation in Polish foreign policy may be explained with the use of Graham Allison’s decision-making models. In somewhat simplified terms, it may be said that S. Meller entered the government hoping that the shaping of Polish foreign policy would be based on the rational actor model. Thus, the state as a unitary actor would define the aim of foreign policy as well as the way of its implementation, choosing the best option. The fact that the minister of foreign affairs was not a member of the party forming the government might have been an advantage as he could have helped to unite different groups and build a cross-party consensus. In practice, however, Polish foreign policy became entangled in current internal political struggle, as the polarization of the political scene between the Law and Justice Party (PiS) and the Civic Platform Party (PO) grew. The problems emerged both on the personal plane among the main decision-makers and among institutions forming Polish foreign policy. During the tenure of S. Meller the centre of gravity of the rational actor model moved towards the organizational process and bureaucratic politics models. The significant increase in the importance of internal determinants that began in 2005 should be taken into consideration in the analysis of Polish foreign policy.